Adaptive macro spatial modulation for mmWave dense networks - Luo, Sheng (2021)
In this letter, an adaptive macro spatial modulation scheme is proposed for the uplink of a millimeter-wave dense network. In the proposed scheme, a user equipment (UE) adaptively establishes communication links with multiple small base stations (SBSs) and switches its beam direction between these SBSs according to part of its transmitting information. We first model the optimal signal transmission scheme that minimizes system symbol-error rate (SER) as an optimization problem and propose an iterative method with relative high computational complexity to solve it. To reduce the complexity, an approximation scheme is also provided, by ignoring the side lobe of the UE. Numerical results show that both proposed schemes can effectively reduce the system SER.